Shifting Consumer Attitudes and Willingness to Pay for Premium Products — The Case of Unibic Cookies - Jain, Akshat; Jain, Prateek (Indian Journal of Marketing, 2024)
Purpose : The objective of this business case was to study and analyze how a new entrant could succeed in a highly competitive industry. The case described the various strategies undertaken by Unibic Foods India Pvt. Ltd. (Unibic) to create and strengthen its position in the highly competitive Indian biscuit industry. Methodology : A detailed analysis of various aspects of Unibic’s business was carried out, including its financial data. The early history of Unibic Foods India Pvt. Ltd. was studied, followed by the analysis of quality-based positioning utilized by Unibic to enter the niche premium cookie segment. A detailed study was done about Unibic’s marketing and promotional strategies. Aspects like Unibic’s key management personnel, product development and advertising strategies, and financial position were also analyzed in depth. Findings : This case highlighted the various techniques deployed by Unibic to enter and succeed successfully in the highly competitive Indian biscuit industry. It helped in decoding the different strategies a new market entrant can deploy to succeed. It also provided insights into the major challenges a new company faces and how it should deal with them. Practical Implications : Entering a new market in a highly competitive industry could be challenging for a new entrant. This business case identified and analyzed strategies Unibic employed to enter and succeed in a highly competitive sector fraught with heavy competitors. The lessons from this business case could help new companies and businesses enter and succeed in competitive markets. The case imparted valuable learning on various aspects of marketing, strategy, and entrepreneurship to the learners. Originality : Each industry has its own unique challenges and level of competition. This business case analyzed an industry through a detailed study of a player, resulting in many useful findings about the industry and the players.